2020
DOI: 10.1111/gbb.12659
|View full text |Cite
|
Sign up to set email alerts
|

Task phase‐specific involvement of the rat posterior parietal cortex in performance of the TUNL task

Abstract: The posterior parietal cortex (PPC) participates in cognitive processes including working memory (WM), sensory evidence accumulation, and perceptually guided decision making. However, surprisingly little work has used temporally precise manipulations to dissect its role in different epochs of behavior taking place over short timespans, such as WM tasks. As a result, a consistent view of the temporally precise role of the PPC in these processes has not been described. In the present study, we investigated the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…A 5‐s timeout period is universally applied. Throughout Punish Incorrect, Initial TUNL, and Full TUNL Training, a performance accuracy criterion of around 70%‐80% of stable performance is promoted (Anderson et al., 2020; Davies et al., 2017; Horner et al., 2013; Hurtubise et al., 2017; Lee et al., 2020; Oomen et al., 2013; Scott et al., 2019, 2021). There has, however, been the rare occasion where the required performance was set at a stable performance accuracy of above 50% (McAllister et al., 2013).…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…A 5‐s timeout period is universally applied. Throughout Punish Incorrect, Initial TUNL, and Full TUNL Training, a performance accuracy criterion of around 70%‐80% of stable performance is promoted (Anderson et al., 2020; Davies et al., 2017; Horner et al., 2013; Hurtubise et al., 2017; Lee et al., 2020; Oomen et al., 2013; Scott et al., 2019, 2021). There has, however, been the rare occasion where the required performance was set at a stable performance accuracy of above 50% (McAllister et al., 2013).…”
Section: Commentarymentioning
confidence: 99%
“…Following the acquisition of all the contributing rules, and with sufficient opportunity to practice the combinations of the rules in the Full TUNL task, specific probing sessions can now be implemented. During the Full TUNL task, the delay period is increased to around a 6‐s delay, with slight fluctuation by a second or two between researchers (Anderson et al., 2020; Davies et al., 2017; Horner et al., 2013; Hurtubise et al., 2017; Lee et al., 2020; Oomen et al., 2013; Scott et al., 2019, 2021). The delay period and resulting cognitive load can be dictated by the intended pharmacological intervention and evaluated parameters.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Though perseverative errors were greater in XY than XX mice, SCC did not impact regressive errors or the number of trials required to reach criterion, suggesting that learning strategy but not overall learning rate is affected by SCC. Another example of subprocess sensitivity is Scott and colleagues' 10 trial unique nonmatch to location (TUNL) task, a test of spatial working memory in rats. Scott et al found that intraposterior parietal cortex intracranial electrical stimulation impaired TUNL accuracy, without affecting response latencies to the sample, providing evidence that rat posterior parietal cortex is required in maintaining a representation of stimuli over a delay period, but not in the encoding of sample stimuli.…”
mentioning
confidence: 99%